Policing and community safety in northern Canadian communities: challenges and opportunities for crime prevention - Griffiths, Curt T. (Crime prevention and community safety, 2019)
Although there is an emerging body of research literature on rural policing, less is known about policing in small communities in Canada’s territories populated largely by Indigenous peoples. These communities are often situated in geographically isolated areas, are subjected to harsh weather conditions, and may experience high rates of crime and disorder. Drawing on interviews conducted with RCMP officers in the two Canadian territories of Yukon and Nunavut, this paper examines the dynamics of policing in northern communities and how these might affect efforts to create sustainable, effective crime prevention initiatives. The findings reveal that geographic isolation, social problems, and history of distrust of the police, combined with the structure through which police services are delivered, present significant challenges to the development and sustainability of crime prevention initiatives. The unique environments of northern communities, however, also provide opportunities for the creation of police-community partnerships built on mutual trust that can provide the basis for effective crime prevention programs.